1979
DOI: 10.1016/s0022-5347(17)56311-9
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Receptors in the Prostate

Abstract: Specific receptors for dihydrotestosterone and estradiol-17-beta have been identified in cytosols of the human and baboon prostate. Binding of radioactive estradiol-17-beta to the 0.4 M potassium chloride extractable component of human prostate nuclei also was demonstrated. Cyproterone acetate and diethylstilbestrol, agents of known high affinity for dihydrotestosterone and estradiol-17-beta receptors, respectively, did not bind significantly to sex hormone binding globulin and, therefore, were useful as compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

1981
1981
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…Additionally, the abilities of unlabelled oestradiol and DES but not progesterone or DHT to compete for the binding of [3H]oestradiol provide support for the specific nature of this binding component. An essentially similar pattern of steroid specificity has been reported for the cytoplasmic oestradiol receptors in the prostate of other species, (Chaisiri et al 1978;Karr et al 1979;Markland & Lee, 1979) as well as in classical oestrogen target organs (King & Mainwaring, 1974). Our data on steroid specificity are consistent with those reported by Pertshuk, Zava, Tobin, Brigati, Gaetjens, Macchia, Wise, Wax & Kim (1979) who employed a histofluorometric technique for the identification of an oestrogen-binding protein in the cytoplasmic and nuclear compartments of human BPH tissues.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, the abilities of unlabelled oestradiol and DES but not progesterone or DHT to compete for the binding of [3H]oestradiol provide support for the specific nature of this binding component. An essentially similar pattern of steroid specificity has been reported for the cytoplasmic oestradiol receptors in the prostate of other species, (Chaisiri et al 1978;Karr et al 1979;Markland & Lee, 1979) as well as in classical oestrogen target organs (King & Mainwaring, 1974). Our data on steroid specificity are consistent with those reported by Pertshuk, Zava, Tobin, Brigati, Gaetjens, Macchia, Wise, Wax & Kim (1979) who employed a histofluorometric technique for the identification of an oestrogen-binding protein in the cytoplasmic and nuclear compartments of human BPH tissues.…”
Section: Discussionsupporting
confidence: 74%
“…Using tissue from patients with benign hyperplasia of the prostate, evidence for the presence of oestradiol and its close relationship to dihydrotestosterone and 5cc-androstane3a,17ß-diol has recently been presented by Ghanadian & Puah (1981). In addition to the existence of oestradiol in the prostate, the presence of cytoplasmic oestrogen receptors has been reported in the prostate of the rat (Armstrong & Bashirelahi, 1978), dog (Chaisiri, Volotaire, Brownen, Evans & Pierrepoint, 1978), baboon (Karr, Sufrin, Kirdani, Murphy & Sandberg, 1978) and normal man (Karr, Wajsman, Madajewicz, Kirdani, Murphy & Sandberg, 1979). However, data with regard to the presence of this receptor in the benign hypertrophied human prostate (BPH) has been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing attention has been given to the roles of estrogens as factors which function in concert with androgens and lead to prostate hypertrophy. The findings of epidemiological studies [9][10][11][12][13], studies employing culture systems for human hyperplastic prostate tissue [14,15], studies employing a prostatic hyperplasia model created by hormone induction in castrated dogs [16,17], and other research indicate that estrogens, in addition to androgens, play important roles in the development of prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years several lines of evidence support a role of estrogen in the pathogenesis and maintenance of BPH, i.e., in humans, a shift in the estrogen/androgen balance in favor of estrogens is arising with age [7][8][9], and it has been shown that the estrogen concentration in the blood and BPH tissue [10,11], and the amount of excretion of estrogen in urine, are high in BPH patients [12]. Moreover, it has been demonstrated that estrogen receptors (ER) exist in the stroma of the human prostate gland [13], and that estrogen enhances the androgen responsiveness of stroma cells derived from the human hyperplastic prostate [14]. These and other research findings thus provide strong evidence of the involvement of estrogen in BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Thus some researchers found benign prostatic hyperplasia (BPH) to be ER positive while others reported negative data [1, 2, 3, 4]. Recent investigations using monoclonal antibodies against ER–α mostly point to a presence of the receptor in prostate tissue, possibly with the dominant presence in stromal cells [5, 6, 7].…”
Section: Introductionmentioning
confidence: 99%